Effects of downhill walking training on aerobic and neuromuscular fitness of young adults - Lima, Leonardo Coelho Rabello De [UNESP]; Oliveira, Thiago Pires De [UNESP]; Oliveira, Felipe Bruno Dias De [UNESP]; Santos, Fernanda Fioravantiazank Dos; Assumpção, Claudio De Oliveira; Greco, Camila Coelho [UNESP]; Denadai, Benedito Sérgio [UNESP] (Universidade Federal de Santa Catarina, 2015)
Eccentric exercise training using low intensity-high volume approach has been performed to improve maximal muscle strength and power. The aim of this study was to compare the effects of short-term downhill walking and level walking training on lower limb strength and maximal oxygen uptake of active individuals. Eighteen young adults were divided into level walking group (n = 9) or downhill walking training group (n = 9). Both groups performed a four-week training program. The level walking group performed seven level walking sessions per week, while the downhill walking group walked downhill (-16%) in the same weekly frequency. One week before and one week after the training protocol, maximal oxygen uptake, muscle-bone cross-sectional area and isometric peak torque of knee extensors and plantar flexors were assessed for both groups. A significant group vs. time interaction was found only for cross sectional area of plantar flexors (PF), showing increases for the downhill walking group (112.6 ± 28.9 cm2 vs. 115.9 ± 29 cm2) but not for the level walking group (94.9 ± 23.3 cm2vs. 94.6 ± 228 cm2). Maximal oxygen uptake remained unaltered after training for both groups and IPT was increased after training for both groups. It was concluded that short-term downhill walking training does not seem to be efficient in promoting improvements in cardiorrespiratory fitness of young adults. However, it seems to promote gains in some variables related to neuromuscular fitness.

O treinamento excêntrico de baixa intensidade e alto volume vem sendo adotado para desenvolver a força e a potência muscular. O objetivo deste estudo foi comparar os efeitos do treinamento de caminhada em declive e em plano, em parâmetros de força de membros inferiores e consumo máximo de oxigênio de indivíduos ativos. Dezoito adultos foram separados em grupos de treinamento em plano (GTP - n = 9) em declive (GTD - n = 9). Ambos realizaram um programa de treinamento de 4 semanas. O GTP realizou sete sessões semanais de caminhada no plano, enquanto o GTD caminhou em declive (-16%). Uma semana antes e uma semana após o treinamento, foram medidos o consumo máximo de oxigênio, área de secção transversa músculo-óssea e o pico de torque isométrico dos extensores do joelho e flexores plantares dos participantes. Interação significante grupo-tempo foi identificada apenas para a área de secção transversa dos flexores plantares, demonstrando aumentos para o grupo GTD (112,6 ± 28,9 cm2vs. 115,9 ± 29 cm2), mas não para o GTP (94,9 ± 23,3 cm2vs. 94,6 ± 228 cm2). O consumo máximo de oxigênio permaneceu inalterado após o treinamento para ambos os grupos e o pico de torque isométrico aumentou significantemente após o treinamento para ambos os grupos. Concluímos, então, que um treinamento de caminhada em declive de curto prazo parece não ser eficiente na promoção de melhoras significativas de parâmetros cardiorrespiratórios de adultos jovens, embora seja efetivo no incremento de algumas variáveis relacionadas à aptidão neuromuscular.
Efeitos da caminhada em declive na aptidão aeróbia e neuromuscular em adultos jovens
Keywords: Muscle strength; Physical endurance; Physical fitness; Aptidão física; Força muscular; Resistência física